Food crises in the Sahel - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Preventing food crises in the Sahel: Ten years of network experience in action. 1985 - 1995. Edited by J Egg and J-J Gabas. 1997. 200 pp. ISBN 92 64 15406 X OECD Publications 2 rue André-Pascal, 75775 Paris Cedex 16 France. Website: http://www.o